RESILIENCE OF THE HUMAN FETAL LUNG FOLLOWING STILLBIRTH: Potential relevance for pulmonary regenerative medicine. - De Paepe, Monique E. (2011)
Recent advances in pulmonary regenerative medicine have increased the demand for alveolar epithelial progenitor cells. Fetal lung tissues from spontaneous pregnancy losses may represent a neglected, yet ethically and societally acceptable source of alveolar epithelial cells. The aim of this study was to determine the regenerative capacity of fetal lungs obtained from second trimester stillbirths. Lung tissues were harvested from 11 stillborn fetuses (13–22 weeks’ gestation) at post-delivery intervals ranging from 10 to 41 hours and grafted to the renal subcapsular space of immune suppressed rats to provide optimal growth conditions. Histology, epithelial and alveolar type II cell proliferation, and surfactant protein-C mRNA expression were studied in preimplantation lung tissues and in xenografts at post-transplantation week 2. All xenografts displayed advanced architectural maturation compared with their respective preimplantation tissues, regardless of gestational age and post-delivery interval. The proliferative activity of the grafts was significantly higher than that of the preimplantation tissues (mean Ki-67 labeling index 26.7 ± 7.7% versus 14.7 ± 10.5%, P < 0.01). The proliferative activity of grafts obtained after a long (> 36 h) post-delivery interval was significantly higher than that of the corresponding preimplantation tissue, and equivalent to that of grafts obtained after a short post-delivery interval (< 14 h). The regenerative capacity of fetal lung tissue was greater at younger (13–17 weeks) than at older (19–22 weeks) gestational ages. The presence of inflammation/chorioamnionitis did not appear to affect graft regeneration. All grafts studied displayed robust surfactant protein-C mRNA expression. In conclusion, fetal lung tissues from second trimester stillbirths can regain their inherent high regenerative potential following short-term culture, even if harvested more than 36 hours after delivery.